Take this car and plug it [plug-in hybrid vehicles]. - Jones, W.D.
This paper presents hybrid cars with a bigger battery packs that can recharge from wall outlets. The resulting machines, referred to as plug-in hybrids, can be propelled exclusively by their electric motors for, in some cases, more than 30 kilometers without their gasoline engines even turning on. The advantages and disadvantages of these cars are discussed in this paper.
Keywords: Toyota Prius; Battery packs; Electric motors; Fuel economy; Hybrid electric cars; Hydrogen economy; Hydrogen fuel cell powered cars; Plug-in hybrids; Wall outlets